The Struggle for Spiritual Authority from the Holy Land to Indonesia: Reference from the Tarekat Naqshabandiyya Jabal Hindi (TNJH) in North Sumatra - Uqbatul Khoir Rambe; Nurliana Damanik; Aprilinda M Harahap (Department of Aqidah and Islamic Philosophy, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2020)
This article discusses the struggle for spiritual authority between Sulaymān al-Zuhdī as “Shaykh Jabal Abi Qubais” and Khalil Hamdi Basya as “Shaykh Jabal Hindi.” The conflict occurred in several stages from the beginning, and finally, Hamdi Basya moved on to Sulaymān al-Zuhdī. Although this clash of the leadership in the Tarekat Naqshabandiyya Khālidiyya (TNK) occurred in the holy land in Mecca, it also influences Indonesia. While the Tarekat Naqshabandiyya Jabal Abi Qubis (TNJAQ) network is barely found in Indonesia, the trail of the Tarekat Naqshabandiyya Jabal Hindi (TNJH) was encountered. By analyzing through a historical approach and interviewing several authoritative individuals, the research discovered that TNJH has been developing in Indonesia, especially in North Sumatra, and has widely spread within some areas, particularly Medan, Binjai, and Deli Serdang. It was also found that this Sufi order primaries the balance of dhikr al-qalb and dhikr al-‘aql by mentioning Allah and paying attention to the creation in the process of tazkīyat al-nafs.